Do European agroforestry systems enhance biodiversity and ecosystem services? A meta-analysis - Torralba, Mario; Fagerholm, Nora; Burgess, Paul J.; Moreno, Gerardo; Plieninger, Tobias (Elsevier, 2016)
Agroforestry has been proposed as a sustainable agricultural system over conventional agriculture and forestry, conserving biodiversity and enhancing ecosystem service provision while not compromising productivity. However, the available evidence for the societal benefits of agroforestry is fragmented and does often not integrate diverse ecosystem services into the assessment. To upscale existing case-study insights to the European level, we conducted a meta-analysis on the effects of agroforestry on ecosystem service provision and on biodiversity levels. From 53 publications we extracted a total of 365 comparisons that were selected for the meta-analysis. Results revealed an overall positive effect of agroforestry (effect size = 0.454, p < 0.01) over conventional agriculture and forestry. However, results were heterogeneous, with differences among the types of agroforestry practices and ecosystem services assessed. Erosion control, biodiversity, and soil fertility are enhanced by agroforestry while there is no clear effect on provisioning services. The effect of agroforestry on biomass production is negative. Comparisons between agroforestry types and reference land-uses showed that both silvopastoral and silvoarable systems increase ecosystem service provision and biodiversity, especially when compared with forestry land. Mediterranean tree plantation systems should be especially targeted as soil erosion could be highly reduced while soil fertility increased. We conclude that agroforestry can enhance biodiversity and ecosystem service provision relative to conventional agriculture and forestry in Europe and could be a strategically beneficial land use in rural planning if its inherent complexity is considered in policy measures.
Keywords: Land use management; Systematic review; Silvopastoral systems; Silvoarable systems; Agroecosystem